Institute of the Commissioner for the Resorts of the Caucasian Mineral Waters (1934–1937) - Zaven V., Akopyan (Kavkazologiya, 2023)
This article constitutes a continuation of a publication series exploring the historical backdrop of the North Caucasus Region, focusing on the period when the administrative hub of this vast region re-sided in the resort city of Pyatigorsk (1934 - early 1937). Its primary focus resides with the State Institute of Commissioners, operating under the auspices of the Central Executive Committee of the USSR, overseeing the resorts of the Caucasian Mineral Waters (CMW, Kavminvody). Throughout this time frame, Professor V.N. Semenov, at the helm of the Architectural and Planning Workshop within the People's Commissariat of Public Utilities of the RSFSR, crafted a comprehensive project to propel the CMW resorts to new heights. The entrusted execution of this project was assigned to authorized representatives of the Central Executive Committee of the USSR, vested with signifi-cant powers. Occupying the post of director of the Caucasian Mineral Waters in the 1920s and 30s (and since 1935, also serving as the commissioner of the CEC of the USSR), were esteemed indi-viduals such as S.A. Mamushin, M.I. Ganshtak, A.S. Enukidze, and A.D. Metelev, who skillfully assumed the helm of both Kavminvody and Sochi resorts. The author posits that at this juncture, we should not disregard the invaluable lessons learned from the successful operation of this institute. As a prospective option, the prospect of establishing a dedicated institute for the management of CMW resorts warrants consideration, potentially involving the plenipotentiary representative of the President in the North Caucasus Federal District.